Answer:
![a_(n+1)=a_n+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tqcfjw8lzowgr1m93cd0aj7bcor63a14px.png)
Explanation:
Have in mind the definition of the term
, and now work on what the term
is based on the previous definition:
![a_(n+1) = 4\,(n+1)-1\\a_(n+1)=4\,n+4-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iues8w5arhkrxngjqao9biebx6npbb0j2y.png)
In the next step do NOT combine the numerical values, but try to identify the
term (
) in the expression (notice the use of square brackets to group the relevant terms):
![a_(n+1)=4\,n+4-1\\a_(n+1)=[4\,n-1]+4\\a_(n+1)=a_n+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/on2g0wuav9xbll0fi9i9pujnqihletq893.png)
So now we have the term "
" defined in a recursive manner based on the previous term "
"